A modified toughened particle and its preparation method and application as well as a tough ceramic material and its preparation method and application

By using modified toughening particles in dental restoration materials and forming an organic adsorption layer through chemical bonding, the problem of poor fracture toughness of resin ceramic composite materials is solved, and the high fracture toughness and elastic modulus of ceramic materials are achieved, and brittle fracture is avoided.

CN119775504APending Publication Date: 2025-04-08AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411985502.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing resin ceramic composite materials have poor fracture toughness during use, which can easily lead to maxillofacial fracture and affect the oral health of patients.

Method used

Modified toughening particles are used to form an organic adsorption layer by chemically bonding the polymer to silane compounds, increasing its interface bonding force with inorganic fillers, and forming a "sea-island" structure to improve the fracture toughness of the material.

Benefits of technology

Modified toughening particles significantly improve the fracture toughness and elastic modulus of ceramic materials, avoid brittle fracture, slow down patients' discomfort, and take into account the strength and hardness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223524500000091
    Figure BDA0005223524500000091
  • Figure BDA0005223524500000092
    Figure BDA0005223524500000092
  • Figure BDA0005223524500000101
    Figure BDA0005223524500000101
Patent Text Reader

Abstract

The present invention belongs to the field of dental restoration technology, and specifically relates to a modified toughening particle and a preparation method and application thereof, as well as a tough ceramic material and a preparation method and application thereof. Compared with traditional impact resistance agents, the modified toughening particles provided by the present invention modify the polymer by silanization, and form an organic adsorption layer on the outer layer by chemical bonding, which increases its interface bonding force with the inorganic filler, so that it has good compatibility and interface bonding with the system, which makes it evenly dispersed in the repair composition, and the dispersed particles gradually gather to form an island structure. When the material is impacted by external force, the modified toughening particles are stress concentration points, causing deformation, and inducing silver streaks and shear bands around them. The silver streaks and shear bands disperse and absorb the impact energy, forming a transition from brittle fracture to tough fracture of the material, thereby achieving the purpose of toughening. The tough ceramic material provided by the present invention improves the fracture toughness of the ceramic material by adding the above-mentioned modified toughening particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dental restoration, and in particular relates to a modified toughening particle and a preparation method and application thereof, as well as a tough ceramic material and a preparation method and application thereof. Background Art

[0002] With the continuous development of dental restoration technology, traditional dental restoration materials, such as alloy materials and porcelain materials, are gradually being replaced by resin composite materials with excellent mechanical properties and good biocompatibility due to their insufficient mechanical properties, easy breakage during use causing secondary damage, and poor biocompatibility.

[0003] At present, resin-ceramic composites are widely used in clinical practice. Resin-ceramic composites have similar mechanical properties and good machinability to natural teeth, which enables them to perform well in the anatomical morphology, marginal adaptability and color matching of the restoration, and are widely used in the restoration of inlays.

[0004] However, resin-ceramic composite materials have poor fracture toughness and may cause maxillofacial fractures during use, affecting the oral health of patients and limiting the development of resin-ceramic composite materials. Summary of the invention

[0005] The purpose of the present invention is to provide a modified toughening particle and a preparation method and application thereof, as well as a tough ceramic material and a preparation method and application thereof. The modified toughening particle provided by the present invention can give the tough ceramic material high fracture toughness.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The invention provides a modified toughened particle, comprising a polymer and an organic adsorption layer chemically bonded on the surface of the polymer; the organic adsorption layer comprises a silane compound; the polymer comprises one or more of a thermoplastic resin, an elastomer and an unsaturated rubber.

[0008] Preferably, the thermoplastic resin includes one or more of a homopolymer resin and a copolymer resin.

[0009] Preferably, the homopolymer resin includes one or more of polyethersulfone, chlorinated polyethylene and polyphenylene ether ketone; the copolymer resin includes one or more of methyl methacrylate-butadiene-styrene terpolymer, acrylonitrile-butadiene-styrene copolymer and ethylene-vinyl acetate copolymer.

[0010] Preferably, the elastomer is a thermoplastic elastomer.

[0011] Preferably, the unsaturated rubber includes one or more of ethylstyrene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, carboxylated nitrile rubber, ethylene-propylene rubber, styrene-butadiene rubber and chloroprene rubber.

[0012] Preferably, the silane compound includes one or more of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0013] Preferably, the average particle size of the modified toughening particles is 100 to 1000 nm.

[0014] Preferably, the mass ratio of the polymer to the organic adsorption layer is 85-95:15-5.

[0015] The present invention also provides a method for preparing the modified toughened particles described in the above scheme, comprising the following steps:

[0016] The polymer, acid, silane compound and solvent are mixed to carry out coupling reaction to obtain the modified toughened particles.

[0017] Preferably, the coupling reaction temperature is 70-100° C., and the insulation reaction time is 2-4 hours.

[0018] The present invention also provides the use of the modified toughening particles described in the above scheme or the modified toughening particles obtained by the preparation method described in the above scheme in the preparation of dental restoration materials.

[0019] The present invention also provides a tough ceramic material, comprising the following components in percentage by mass:

[0020] 20-40% organic resin precursor, 50-70% inorganic filler, 2-10% modified toughening particles, 0.2-0.3% initiator, and 0-0.06% colorant; the organic resin precursor includes one or more of a prepolymer and a resin monomer; the modified toughening particles are the modified toughening particles described in the above scheme or the modified toughening particles obtained by the preparation method described in the above scheme.

[0021] Preferably, the prepolymer is one or more of a polyolefin prepolymer and a polyester prepolymer; and the resin monomer is an acrylate monomer.

[0022] Preferably, the inorganic filler includes one or more of silicate, sulfate, oxide, fluoride and glass powder.

[0023] The present invention also provides a method for preparing the tough ceramic material described in the above scheme, comprising the following steps:

[0024] The prepolymer, resin monomer, inorganic filler, modified toughening particles, initiator and colorant are mixed and then pressed to carry out polymerization reaction to obtain the tough ceramic material.

[0025] Preferably, the pressing is carried out in a mold; the pressing temperature is 120-130° C., the pressure is 3-8 MPa, and the heat and pressure holding time is 25-32 hours.

[0026] The present invention also provides the use of the tough ceramic material described in the above scheme or the tough ceramic material obtained by the preparation method described in the above scheme in the preparation of dental restorations.

[0027] The present invention provides a modified toughening particle. Compared with the traditional impact-resistant agent, the modified toughening particle provided by the present invention modifies the polymer by silanization, and forms an organic adsorption layer on the outer layer by chemical bonding, which increases the interface bonding force between the particle and the inorganic filler, and makes it have good compatibility and interface bonding with the system, so that it is evenly dispersed in the repair composition, and the dispersed particles gradually gather to form a "sea-island" structure. When the material is impacted by external force, the modified toughening particle is a stress concentration point, causing it to deform, and inducing silver streaks and shear bands around it, which disperse and absorb the impact energy through the silver streaks and shear bands, forming a transition from brittle fracture to ductile fracture of the material, thereby achieving the purpose of toughening.

[0028] The present invention also provides a method for preparing the modified toughened particles described in the above scheme. The preparation method provided by the present invention has low cost, good safety, and is easy to be applied in industrial production.

[0029] The present invention also provides the use of the modified toughening particles described in the above scheme or the modified toughening particles obtained by the preparation method described in the above scheme in the preparation of dental restoration materials. The modified toughening particles provided by the present invention can give the material good fracture toughness and elastic modulus, taking into account both strength and hardness, and have broad application prospects in the field of dental restoration.

[0030] The present invention provides a tough ceramic material. The tough ceramic material provided by the present invention has high fracture toughness and high elastic modulus, and the fracture toughness is 1-3MPa / m 2 , elastic modulus is 6-8GPa, flexural strength is 140-200MPa, hardness is 30-50HV1, and comprehensive performance is excellent. The present invention improves the fracture toughness of the ceramic material by adding the modified toughening particles of the above scheme. The modified toughening particles can absorb energy and disperse it into the ceramic material to reduce the impact or stress. In terms of microstructure, the modified toughening particles interact with the matrix material to form a composite structure to prevent the propagation of fracture, thereby achieving the purpose of toughening.

[0031] The present invention also provides a method for preparing the tough ceramic material of the above scheme. The present invention adds modified toughening particles into the ceramic material to improve the mechanical properties of the material such as toughness, with simple steps and convenient operation.

[0032] The present invention also provides the use of the tough ceramic material described in the above scheme or the tough ceramic material obtained by the preparation method described in the above scheme in the preparation of dental restorations. The tough ceramic material provided by the present invention has high fracture toughness and high elastic modulus, can effectively avoid brittle fracture of resin-based ceramic composite materials when used as veneer restorations, and alleviate the discomfort of patients. DETAILED DESCRIPTION

[0033] The invention provides a modified toughened particle, comprising a polymer and an organic adsorption layer chemically bonded on the surface of the polymer; the organic adsorption layer comprises a silane compound.

[0034] The modified toughened particles provided by the present invention include polymers; the polymers preferably include one or more of resins, elastomers and rubbers; the polymers are preferably core-shell structure polymers.

[0035] In the present invention, the resin is preferably a thermoplastic resin; the thermoplastic resin preferably includes one or more of a homopolymer resin and a copolymer resin; the homopolymer resin preferably includes one or more of polyethersulfone, chlorinated polyethylene and polyphenylene ether ketone; the copolymer resin preferably includes one or more of a methyl methacrylate-butadiene-styrene terpolymer (core-shell structure polymer), an acrylonitrile-butadiene-styrene copolymer and an ethylene-vinyl acetate copolymer.

[0036] In the present invention, the elastomer is preferably a thermoplastic elastomer; the thermoplastic elastomer is preferably a styrene-based thermoplastic elastomer; the styrene-based thermoplastic elastomer is preferably a styrene-butadiene thermoplastic elastomer.

[0037] In the present invention, the rubber is an unsaturated rubber; the unsaturated rubber preferably includes one or more of ethylstyrene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, carboxylated nitrile rubber, ethylene propylene rubber, styrene butadiene rubber and chloroprene rubber. The present invention forms a "sea-island" phase structure by using the above polymers. When the material is impacted by external force, these dispersed "core" (polymer) particles will become stress concentration points, causing the surrounding matrix to deform, thereby absorbing and dispersing the impact energy, preventing the expansion of cracks, and thus improving the toughness of the material.

[0038] The modified toughened particles provided by the present invention include an organic adsorption layer; the silane compound preferably includes one or more of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0039] In the present invention, the mass ratio of the polymer to the organic adsorption layer is preferably 85-95:15-5, specifically 87:13 or 92:8. The present invention improves the surface energy of the material through the above mass ratio, thereby enhancing its bonding with the resin.

[0040] In the present invention, the average particle size of the modified toughening particles is 100-1000 nm, specifically 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm. The present invention achieves better dispersion in the system through the above particle size.

[0041] The present invention also provides a method for preparing the modified toughened particles described in the above scheme, comprising the following steps:

[0042] The polymer, acid, silane compound and solvent are mixed (referred to as the first mixing) to carry out a coupling reaction to obtain the modified toughened particles.

[0043] In the present invention, the acid is preferably an organic acid; the organic acid is preferably a C1-C10 organic acid; the C1-C10 organic acid is preferably acetic acid. The present invention improves the stability of the reaction system by using the acid.

[0044] In the present invention, the mass ratio of the polymer to the acid is preferably 99.9-99.6:0.1-0.4, and specifically may be 99.7:0.3.

[0045] In the present invention, the silane compound preferably includes one or more of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0046] In the present invention, the mass ratio of the polymer to the silane compound is preferably 75-85:25-15, specifically 77:23, 79:21, 80:20 or 82:18.

[0047] In the present invention, the solvent is preferably a polar solvent; the polar solvent preferably includes one or more of alcohol and water; the alcohol is preferably ethanol; and the water is preferably deionized water.

[0048] In the present invention, the mass ratio of the polymer to the solvent is preferably 20-30:80-70, specifically 22:78, 25:75 or 28:72.

[0049] In the present invention, the first mixing is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 395-405 rpm, specifically 400 rpm, and the mixing time is preferably 30-40 min, specifically 35 min or 37 min.

[0050] In the present invention, the temperature of the coupling reaction is preferably 70-100°C, specifically 80°C or 90°C, and the insulation reaction time is preferably 2-4h, specifically 3h. The present invention improves the surface energy of the material through the coupling reaction, thereby enhancing its bonding with the resin.

[0051] The present invention also provides the use of the modified toughening particles described in the above scheme or the modified toughening particles obtained by the preparation method described in the above scheme in the preparation of dental restoration materials.

[0052] The modified toughened particles provided by the present invention can give the material good fracture toughness and elastic modulus, taking into account both strength and hardness, and can be used in products such as dental restoration materials, and have broad application prospects in the field of dental restoration.

[0053] The present invention also provides a tough ceramic material, comprising the following components in percentage by mass:

[0054] 20-40% organic resin precursor, 50-70% inorganic filler, 2-10% modified toughening particles, 0.2-0.3% initiator, and 0-0.06% colorant; the organic resin precursor includes one or more of a prepolymer and a resin monomer; the modified toughening particles are the modified toughening particles described in the above scheme or the modified toughening particles obtained by the preparation method described in the above scheme.

[0055] The tough ceramic material provided by the present invention comprises 20-40% of the organic resin precursor by mass percentage, specifically 20%, 22%, 25%, 27%, 30%, 32%, 35%, 37% or 40%. The present invention uses the above organic resin precursor as a bonding reinforcement.

[0056] In the present invention, the prepolymer is preferably one or more of a polyolefin prepolymer and a polyester prepolymer; the polyolefin prepolymer preferably includes one or more of polyethylene, polystyrene, polyvinyl chloride, polytetrafluoroethylene and polypropylene; the polyester prepolymer preferably includes one or more of polymethyl acrylate, polyethyl acrylate, polybutyl acrylate and polyethylene glycol dimethacrylate.

[0057] In the present invention, the resin monomer is preferably an acrylate monomer; the acrylate monomer preferably includes one or more of methyl acrylate, ethyl acrylate, butyl acrylate, 2-methyl methacrylate, 2-ethyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-ethoxyethyl acrylate, cyclohexyl acrylate, methyl methacrylate, n-butyl methacrylate, hydroxyethyl methacrylate, carbamate dimethacrylate, glycerol dimethacrylate, neopentyl glycol dimethacrylate, triethylene glycol dimethacrylate (TEGDMA), diurethane dimethacrylate (UDMA), ethylene glycol dimethacrylate (EGDMA), bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and bisphenol A-ethoxy methacrylate glycidyl ester (Bis-EMA).

[0058] The tough ceramic material provided by the present invention comprises 50-70% of inorganic filler in terms of mass percentage, specifically 50%, 53%, 55%, 57%, 60%, 63%, 65%, 67% or 70%. The present invention improves the mechanical properties of the material by using the inorganic filler.

[0059] In the present invention, the inorganic filler preferably includes one or more of silicates, sulfates, oxides, fluorides and glass powder; the silicates preferably include one or more of mica powder, talc, kaolin, montmorillonite, wollastonite powder and feldspar porcelain powder; the sulfates preferably include one or more of barium sulfate and calcium carbonate; the oxides preferably include one or more of aluminum oxide, zirconium oxide, barium oxide, silicon dioxide and quartz powder; the fluorides are preferably ytterbium fluoride; the glass powder preferably includes one or more of barium glass, strontium glass, lanthanum glass and silicate glass.

[0060] In terms of mass percentage, the tough ceramic material provided by the present invention includes 2-10% of modified toughening particles, specifically 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0061] Calculated by mass percentage, the tough ceramic material provided by the present invention includes 0.2-0.3% of the initiator, specifically 0.20%, 0.23%, 0.25%, 0.28% or 0.30%.

[0062] In the present invention, the initiator preferably includes one or more of peroxides, amines and pyrosulfites; the peroxide preferably includes one or more of benzoyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, isopropylbenzene hydroperoxide and tert-butyl hydroperoxide; the amine preferably includes one or more of N,N-dimethylaniline and N,N-diethylaniline; the pyrosulfite is preferably sodium pyrosulfite.

[0063] The tough ceramic material provided by the present invention includes 0-0.06% of colorant in terms of mass percentage, specifically 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or 0.06%. The present invention achieves the beauty and bionic effect of the material by using the above amount of colorant.

[0064] In the present invention, the colorant preferably includes one or more of white, blue, yellow, red, brown and black; the white colorant preferably includes one or more of titanium white, lithopone and titanium dioxide; the blue colorant preferably includes one or more of iron blue and phthalocyanine blue; the yellow colorant preferably includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, lead chrome yellow, iron oxide yellow, chrome yellow and even light yellow; the red colorant preferably includes one or more of scarlet pink, sunset red and iron oxide red; the brown colorant is preferably iron oxide brown; the black colorant preferably includes one or more of iron oxide black and carbon black.

[0065] In the present invention, the modification degree of the tough ceramic material is preferably 4%. The present invention improves the bonding strength between the toughening system (modified toughening particles) and the resin system through the above modification degree.

[0066] The present invention also provides a method for preparing the tough ceramic material described in the above scheme, comprising the following steps:

[0067] The prepolymer, resin monomer, inorganic filler, modified toughening particles, initiator and colorant are mixed (referred to as the second mixing) and then pressed to carry out polymerization reaction to obtain the tough ceramic material.

[0068] In the present invention, the second mixing is preferably: first premixing the prepolymer and the initiator to obtain an initiation system, second premixing the initiation system and the resin monomer to obtain a resin matrix, and third premixing the resin matrix and the inorganic filler.

[0069] In the present invention, the first premixing is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 195-205 rpm, specifically 200 rpm, and the mixing time is preferably 90-150 min, specifically 90 min, 100 min, 110 min, 120 min, 130 min, 140 min or 150 min.

[0070] In the present invention, the second premixing is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 295-305 rpm, specifically 300 rpm, and the mixing time is preferably 120-150 min, specifically 120 min, 130 min, 140 min or 150 min.

[0071] In the present invention, the third premixing is preferably: adding the inorganic filler into the resin matrix in batches while stirring.

[0072] In the present invention, the stirring time is preferably 15 to 20 minutes, specifically 18 minutes; the stirring speed is preferably 10 to 30 rpm, specifically 20 rpm; the stirring times are preferably more than 1 time.

[0073] In the present invention, the number of batch additions is preferably 8 to 10 times, specifically 9 times.

[0074] In the present invention, the pressing is preferably carried out in a mold; the pressing temperature is preferably 120-130°C, specifically 124°C or 127°C, the pressure is preferably 3-8MPa, specifically 5MPa or 7MPa, and the heat and pressure holding time is preferably 25-32h, specifically 27h or 30h.

[0075] In the present invention, after the pressing, the process preferably further comprises cooling the obtained system and then demolding.

[0076] The present invention also provides the use of the tough ceramic material described in the above scheme or the tough ceramic material obtained by the preparation method described in the above scheme in the preparation of dental restorations.

[0077] The tough ceramic material provided by the present invention has high fracture toughness and high elastic modulus, can effectively avoid brittle fracture of the resin-based ceramic composite material when used as a veneer for repair, and alleviate the discomfort of patients.

[0078] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0079] Example 1

[0080] The tough ceramic material provided in this embodiment has components as shown in Table 1.

[0081] Table 1 Composition of tough ceramic materials in Example 1

[0082] Components Mass percentage / wt% Triethylene glycol dimethacrylate TEGDMA 11.685 Ethylene glycol dimethacrylate EGDMA 1.17 Urethane Dimethacrylate UDMA 25.33 Initiator (BPO) 0.21 Modified toughened particles 2.02 Glass powder (barium glass) 57.06 Silicon dioxide 2.31 Titanium Dioxide 0.12 Iron oxide red 0.03 Iron oxide yellow 0.06 Iron Oxide Black 0.005

[0083] The method for preparing the tough ceramic material of this embodiment comprises the following steps:

[0084] (1) Add acetic acid and a silane compound (γ-aminopropyltriethoxysilane) to a polymer (methyl methacrylate-butadiene-styrene terpolymer), ethanol and water, and stir at 400 rpm for 35 minutes to obtain modified toughened particles.

[0085] (2) Triethylene glycol dimethacrylate and an initiator were mixed and stirred at 200 rpm for 120 min to obtain an initiation system.

[0086] (3) The initiator system was mixed with ethylene glycol dimethacrylate and dimethacrylate carbamate, and stirred at 300 rpm for 140 min to obtain a resin matrix.

[0087] (4) Adding the modified toughening particles, colorant and inorganic filler (the inorganic filler is added in 8 batches) into the resin matrix, stirring at 20 rpm for 18 min, stirring once, to obtain a composition.

[0088] (5) placing the composition in a mold for pressing at a pressing temperature of 125° C., a pressure of 5 MPa, and a pressing time of 27 h, and demolding the system after cooling to obtain the tough ceramic material.

[0089] Example 2

[0090] The tough ceramic material provided in this embodiment has components as shown in Table 2, and the preparation method is the same as that in Example 1.

[0091] Table 2 Composition of tough ceramic materials in Example 2

[0092] Components Mass percentage / wt% Triethylene glycol dimethacrylate TEGDMA 10.84 Bisphenol A-bis(glycidyl methacrylate) Bis-GMA 12.13 Urethane Dimethacrylate UDMA 15.33 Initiator (BPO) 0.25 Modified toughened particles (polymer is styrene-butadiene thermoplastic elastomer) 5.26 Glass powder (strontium glass) 48.13 Zirconia 8.06

[0093] Example 3

[0094] The tough ceramic material provided in this embodiment has components as shown in Table 3, and the preparation method is the same as that in Example 1.

[0095] Table 3 Composition of tough ceramic materials in Example 3

[0096]

[0097] Comparative Example 1

[0098] The tough ceramic material provided in this comparative example has components as shown in Table 4.

[0099] Table 4 Comparative Example 1 Toughness Ceramic Material Composition

[0100] Components Mass percentage / wt% Triethylene glycol dimethacrylate TEGDMA 11.685 Ethylene glycol dimethacrylate EGDMA 1.17 Urethane Dimethacrylate UDMA 25.33 Initiator (BPO) 0.21 Toughened particles (methyl methacrylate-butadiene-styrene terpolymer) 2.02 Glass powder (barium glass) 57.06 Silicon dioxide 2.31 Titanium Dioxide 0.12 Iron oxide red 0.03 Iron oxide yellow 0.06 Iron Oxide Black 0.005

[0101] The preparation method of the tough ceramic material of this comparative example comprises the following steps:

[0102] (1) Triethylene glycol dimethacrylate and an initiator were mixed and stirred at 200 rpm for 120 min to obtain an initiation system.

[0103] (2) The initiator system was mixed with resin monomers (ethylene glycol dimethacrylate and dimethacrylate urethane) and stirred at 300 rpm for 140 min to obtain a resin matrix.

[0104] (3) Add toughening particles, colorant and inorganic filler (the inorganic filler is added in 8 batches) into the resin matrix, stir at 20 rpm for 18 min, stir once, and obtain a composition.

[0105] (4) placing the composition in a mold for pressing at a pressing temperature of 125° C., a pressure of 5 MPa, and a pressing time of 27 h, and demolding the system after cooling to obtain the tough ceramic material.

[0106] Comparative Example 2

[0107] The tough ceramic material provided in this comparative example has components as shown in Table 5.

[0108] Table 5 Comparative Example 2 Toughness Ceramic Material Composition

[0109]

[0110]

[0111] The preparation method of the tough ceramic material of this comparative example comprises the following steps:

[0112] (1) Add acetic acid and a silane compound (γ-aminopropyltriethoxysilane) to a polymer (styrene-butadiene), ethanol and water, and stir at 400 rpm for 35 minutes to obtain modified toughened particles.

[0113] (2) Triethylene glycol dimethacrylate and an initiator were mixed and stirred at 200 rpm for 120 min to obtain an initiation system.

[0114] (3) The initiator system was mixed with resin monomers (bisphenol-A-glycidyl methacrylate and dimethacrylate urethane) and stirred at 300 rpm for 140 min to obtain a resin matrix.

[0115] (4) Adding the modified toughening particles and the inorganic filler (the inorganic filler is added in 8 portions) into the resin matrix, stirring at a speed of 20 rpm for 18 min, stirring once, to obtain a composition.

[0116] (5) placing the composition in a mold for pressing at a pressing temperature of 125° C., a pressure of 5 MPa, and a pressing time of 27 h, and demolding the system after cooling to obtain the tough ceramic material.

[0117] Comparative Example 3

[0118] The tough ceramic material provided in this comparative example has components as shown in Table 6.

[0119] Table 6 Comparative Example 3 Toughness Ceramic Material Composition

[0120] Components Mass percentage / wt% Triethylene glycol dimethacrylate TEGDMA 14.24 Bisphenol A-bis(glycidyl methacrylate) Bis-GMA 32.13 Initiator (BPO) 0.29 Modified toughened particles 1.05 Glass powder (barium glass) 50.13 Silicon dioxide 2.16

[0121] The preparation method of the tough ceramic material of this comparative example comprises the following steps:

[0122] (1) Add acetic acid and a silane compound (γ-aminopropyltriethoxysilane) to polymers (acrylonitrile-butadiene-styrene copolymer and ethylene-vinyl acetate copolymer), ethanol and water, and stir at 400 rpm for 35 minutes to obtain modified toughened particles.

[0123] (2) Triethylene glycol dimethacrylate and an initiator were mixed and stirred at 200 rpm for 120 min to obtain an initiation system.

[0124] (3) The initiator system was mixed with the resin monomer bisphenol-A-glycidyl methacrylate, and stirred at 300 rpm for 140 min to obtain a resin matrix.

[0125] (4) Adding the modified toughening particles and the inorganic filler (the inorganic filler is added in 8 portions) into the resin matrix, stirring at a speed of 20 rpm for 18 min, stirring once, to obtain a composition.

[0126] (5) placing the composition in a mold for pressing at a pressing temperature of 125° C., a pressure of 5 MPa, and a pressing time of 27 h, and demolding the system after cooling to obtain the tough ceramic material.

[0127] Test Example 1

[0128] The fracture toughness test was conducted on the tough ceramic materials of Examples 1 to 3 and Comparative Examples 1 to 3. The tough ceramic materials were processed by mechanical processing equipment to prepare 7 samples with a size of 4.0 mm × 3.0 mm × 44 mm. The samples were roughly polished with 800-mesh sandpaper and then finely polished with 2000-mesh sandpaper. The samples were thoroughly cleaned to ensure that all grinding debris was cleaned. The 3 mm wide surface was facing up, and an initial V groove was made on this surface (in this fracture toughness test, this surface was subjected to tension). The V groove was cut along the pencil indicator line with a V-shaped grinding needle or an internal circle slicer so that all samples reached a depth of 1.0 mm. Clean the sample, especially the V groove to remove debris. Use a high-definition microscope to measure and record the V groove depth a of each sample. An electric tensile testing machine (ZQ-2000) was used for testing. A 3 mm wide sample with a V groove was placed face down in the middle of the platform. The test scheme "bending test scheme" was selected, with a span of 40 mm, and the crosshead applied a load to the sample at a speed of 0.5 mm / min. Record the breaking load force, retain 3 significant figures, and calculate according to the following formula in standard GB 30367. The results are shown in Table 7.

[0129]

[0130] Y=1.9472-5.0247a+11.8954a2-18.0635a3+14.5986a4-4.6896a5;

[0131] Where: K lc is the fracture toughness, unit is MPa·m 1 / 2 ; σ is the fracture strength, in megapascals (MPa); P is the fracture load, in meganewtons (MN); w is the width of the specimen, in millimeters (mm); b is the thickness of the specimen, in millimeters (mm); S1 is the support span, in millimeters (mm); Y is the stress intensity shape factor.

[0132] Test Example 2

[0133] The flexural strength and elastic modulus of the tough ceramic materials of Examples 1 to 3 and Comparative Examples 1 to 3 were tested. The tough ceramic materials were processed by mechanical processing equipment to prepare 10 specimens with a size of 1.2 mm × 4.0 mm × 16 mm. They were coarsely polished with 800 mesh sandpaper and then finely polished with 2000 mesh sandpaper. The specimens were cleaned to ensure that they were clean. The dimensions of the specimens were measured with a caliper with an accuracy of 0.01 mm. The tensile testing machine was used for the test at a speed of 1 mm / min, a span of 12 mm, and a test surface of 4.0 mm × 16 mm. The corresponding test parameters were entered, and both sides of the specimens were laid flat on the test platform to ensure that the middle of the specimen was in the middle of the platform. Click to start the test until the specimen broke. At the end of the test, the flexural strength and elastic modulus values ​​were recorded. The results are shown in Table 7.

[0134] Test Example 3

[0135] The Vickers hardness test was performed on the tough ceramic materials of Examples 1 to 3 and Comparative Examples 1 to 3. A Vickers hardness tester was used with a force value of "1" to test the hardness of the tough ceramic materials. The results are shown in Table 7.

[0136] Table 7 Performance test results of tough ceramic materials

[0137] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Fracture toughness / MPa / m 2 > 2.40 2.69 3.15 1.89 2.05 1.89 Flexural strength / MPa 172.153 183.771 213.100 142.000 100.052 165.270 Elastic modulus / GPa 7.25748 7.34096 7.862302 6.65044 3.54163 7.15239 Vickers hardness / HV1 53.4 56.1 65.2 42.43 30.80 59.2

[0138] According to Table 7, by adding a specific content of modified toughening particles, the fracture toughness of the obtained tough ceramic material is significantly higher than that of the comparative example, and the maximum fracture toughness reaches 3.15MPa / m 2 , indicating that the addition of modified toughening particles significantly improves the fracture toughness of the ceramic material; by comparing Example 1 and Comparative Example 1, it can be seen that the fracture toughness of the material after adding modified toughening particles is 2.40MPa / m 2 , the fracture toughness of the unmodified material is 2.05MPa / m 2 , indicating that the interface bonding ability of the modified toughening particles provided by the present invention is improved, thereby improving the performance of the material; it can be seen from Comparative Example 2 that when the content of the modified toughening particles is too much, the strength of the material decreases, and the flexural strength also decreases accordingly; it can be seen from Comparative Example 3 that when the content of the modified toughening particles added is too little, the fracture toughness of the material decreases.

[0139] It can be seen from the above examples that the modified toughened particles provided by the present invention can give the material excellent fracture toughness and elastic modulus, and have high flexural strength and high Vickers hardness.

[0140] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified toughened particle, characterized in that: It comprises a polymer and an organic adsorption layer chemically bonded on the surface of the polymer; the organic adsorption layer comprises a silane compound; and the polymer comprises one or more of a thermoplastic resin, an elastomer and an unsaturated rubber.

2. The modified toughened particles according to claim 1, characterized in that: The thermoplastic resin includes one or more of a homopolymer resin and a copolymer resin.

3. The modified toughened particles according to claim 2, characterized in that: The homopolymer resin includes one or more of polyethersulfone, chlorinated polyethylene and polyphenylene ether ketone; The copolymer resin includes one or more of methyl methacrylate-butadiene-styrene terpolymer, acrylonitrile-butadiene-styrene copolymer and ethylene-vinyl acetate copolymer.

4. The modified toughened particles according to claim 1, characterized in that: The elastomer is a thermoplastic elastomer.

5. The modified toughened particles according to claim 1, characterized in that: The unsaturated rubber includes one or more of ethylstyrene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, carboxylated nitrile rubber, ethylene-propylene rubber, styrene-butadiene rubber and chloroprene rubber.

6. The modified toughened particles according to any one of claims 1 to 5, characterized in that: The silane compound includes one or more of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

7. The modified toughened particles according to any one of claims 1 to 5, characterized in that: The average particle size of the modified toughening particles is 100-1000 nm.

8. The modified toughened particles according to claim 1 or 2, characterized in that: The mass ratio of the polymer to the organic adsorption layer is 85-95:15-5.

9. The method for preparing the modified toughened particles according to any one of claims 1 to 8, characterized in that: The following steps are involved: The polymer, acid, silane compound and solvent are mixed to carry out coupling reaction to obtain the modified toughened particles.

10. The preparation method according to claim 9, characterized in that: The temperature of the coupling reaction is 70-100° C., and the insulation reaction time is 2-4 hours.

11. Use of the modified toughening particles according to any one of claims 1 to 8 or the modified toughening particles obtained by the preparation method according to any one of claims 9 to 10 in the preparation of dental restorative materials.

12. A tough ceramic material, characterized in that: Includes the following components in percentage by mass: 20-40% organic resin precursor, 50-70% inorganic filler, 2-10% modified toughening particles, 0.2-0.3% initiator, 0-0.06% colorant; the organic resin precursor includes one or more of prepolymer and resin monomer; The modified toughening particles are the modified toughening particles according to any one of claims 1 to 8 or the modified toughening particles obtained by the preparation method according to any one of claims 9 to 10.

13. The tough ceramic material according to claim 12, characterized in that: The prepolymer is one or more of polyolefin prepolymer and polyester prepolymer; the resin monomer is an acrylic ester monomer.

14. The tough ceramic material according to claim 12 or 13, characterized in that: The inorganic filler includes one or more of silicate, sulfate, oxide, fluoride and glass powder.

15. The method for preparing the tough ceramic material according to any one of claims 12 to 14, characterized in that: The following steps are involved: The prepolymer, resin monomer, inorganic filler, modified toughening particles, initiator and colorant are mixed and then pressed to carry out polymerization reaction to obtain the tough ceramic material.

16. The preparation method according to claim 15, characterized in that: The pressing is carried out in a mold; the pressing temperature is 120-130° C., the pressure is 3-8 MPa, and the heat preservation and pressure holding time is 25-32 hours.

17. Use of the tough ceramic material according to any one of claims 12 to 14 or the tough ceramic material obtained by the preparation method according to any one of claims 15 to 16 in the preparation of dental restorations.